Antifungal activity of Persicaria odorata extract against anthracnose caused by Colletotrichum capsici and Colletotrichum gloeosporioides - Yanpirat P.; Vajrodaya S. (Penerbit Universiti Kebangsaan Malaysia, 2015)
Anthracnose is the most serious problem in the degradation of fruit quality. Natural plant products are currently the alternative source of fungicides. Persicaria odorata, which is commonly found in Southeast Asia, exhibits antioxidant and antibacterial activity as well as being a source of phenolic compounds. The activity of P. odorata extract against anthracnose caused by Colletotrichum capsici and Colletotrichum. gloeosporioides was investigated in this study. The chemical compounds were tested by employing the TLC technique. Bioautography and microdilution bioassay were also employed for spore germination and mycelium growth, respectively. The results from the TLC technique showed that the chemical constituents of P. odorata were terpenoids, steroids, and other unidentified organic compounds but not alkaloids. The antifungal test of lipophilic extract showed clear zones on the TLC plate of C. gloeosporioides whereas there were no clear zones with C. capsici. With the result of microdilution bioassay, the lipophilic extract concentration inhibited the germination of C. capsici at a minimum inhibitory concentration (MIC) of 625 μg/ml, and 20,000 μg/ml at 24 and 72 hours, respectively. Whereas the minimum concentrations that inhibited the germination of C. gloeosporioides were 2,500 μg/ml, 10,000 μg/ml, 20,000 μg/ml and 20,000 μg/ml at 24, 72, 120, and 168 hours, respectively.